Effect of obesity on lung function test among adults - Salvi, Dhairya; Moradia, Dhanvi (International Journal of Advances in Medicine, 2020)
Background: Obesity is a chronic disease characterized by excessive body fat that causes damage to the individual’s health and is associated with comorbidities such as diabetes and hypertension and vascular dysfunction. This cross-sectional study was carried out with the objective of evaluating the effect of obesity on lung function test in obese but otherwise healthy adults. Methods: It was a cross-sectional study carried out at tertiary care institute of Gujarat, India. It was conducted over a period of 5 months. A total of 240 adult healthy subjects of both sexes were selected randomly belonging to varying socio-economic status. The study subjects were divided into 3 categories (normal body mass index i.e. BMI, overweight, obese). BMI were calculated for the randomly selected subjects from each list till the desired number in each BMI group were attained. Four respiratory parameters viz. forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), forced expiratory volume in 3 seconds (FEV3), and maximum voluntary ventilation (MVV) were used to assess their lung functions. Results: Two hundred and forty subjects (each group having n=80). The mean age of group I, group II and group III were 27.45±6.37, 28.18±6.42 and 28.98±6.74 respectively. Lung volumes showed significant difference in relation to the BMI. FVC and FEV1 show significant decrease. Group III verses group I (p˂0.001 and p˂0.017 respectively) FEV3 showed significant difference between group I and group III and between group II and group III (p˂0.001). MVV was significantly lower in group III when compared to group I. Conclusions: There is decline in pulmonary function in obese as compared to normal weight adults. These findings suggest deleterious effects on ventilatory mechanics caused by obesity, due to probable lung compression (reduction in the expiratory reserve volume i.e. ERV), leading to a compensatory increase in the inspiratory reserve volume (IRV) in an attempt to maintain a constant vital capacity (VC).